2015
DOI: 10.7883/yoken.jjid.2014.149
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Long Noncoding RNA Profile in Human Gastric Epithelial Cell Response to Helicobacter pylori

Abstract: SUMMARY: Long noncoding RNAs (lncRNAs) are an important class of pervasive genes, and their misregulation has been shown in various types of diseases. However, the relationship between lncRNAs and the immune response to pathogen infection has been rarely reported. Helicobacter pylori is a major human pathogenic bacterium that causes gastritis, peptic ulcer disease, mucosa-associated lymphoid tissue lymphoma, and gastric cancer. The regulatory mechanism of the H. pylori-induced immune response is not yet clear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
(12 reference statements)
1
19
0
Order By: Relevance
“…Though the expression pattern of lncRNAs upon H. pylori infection of a gastric epithelial cell line, GES-1, has been studied, the expression pattern of lncRNAs influenced by H. pylori in GES-1 cells was explored using a microarray, revealing the relationship between lncRNAs and H. pylori-associated diseases. 39,40 We explored the expression pattern of lncRNAs in H. pylori-infected AGS cells using RNA-seq which revealed a full-scale lncRNAs map for H. pylori-infected AGS cells and identified seven to eight-times more lncRNAs than microarray. Meanwhile, our study also revealed the lncRNAs expression in H. pylori infected GC cells, which was not reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Though the expression pattern of lncRNAs upon H. pylori infection of a gastric epithelial cell line, GES-1, has been studied, the expression pattern of lncRNAs influenced by H. pylori in GES-1 cells was explored using a microarray, revealing the relationship between lncRNAs and H. pylori-associated diseases. 39,40 We explored the expression pattern of lncRNAs in H. pylori-infected AGS cells using RNA-seq which revealed a full-scale lncRNAs map for H. pylori-infected AGS cells and identified seven to eight-times more lncRNAs than microarray. Meanwhile, our study also revealed the lncRNAs expression in H. pylori infected GC cells, which was not reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The differential expressions of lncRNAs have been widely observed in various cancers [ 34 - 37 ], and their expressional perturbation has been implicated in the development and progression of cancers [ 38 , 39 ]. Several lncRNA signatures have been developed to improve prognosis prediction of cancers, including colorectal cancer [ 40 ], glioblastoma multiforme [ 41 ], breast cancer [ 42 ], lung cancer [ 43 ] and multiple myeloma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes, Helicobacter pylori , and Campylobacter ( C .) concisus as well as TLR ligands has been recently demonstrated in several studies but the functions of these lncRNAs remain to be elucidated (Ilott et al, 2014; Yi et al, 2014; Yang et al, 2015; Zhu et al, 2015; Yang R. et al, 2016; Westermann et al, 2016). …”
Section: Exploring Lncrna Function Through the Analysis Of Neighborinmentioning
confidence: 99%